Factors Influencing the Incidence of Stunting in Children Aged 24-59 Months in the Work Area Muara Delang Health Center, Jambi - Cahyaningrum, Nadya Elsa; Mars, Siwi Pramatama; Suratman (GoAcademica Research & Publishing, 2024)
Stunting can be caused by many factors such as socio-economics, exclusive breastfeeding, parenting patterns, timing of giving MP-ASI, history of infectious diseases, environmental sanitation, and the role of community leaders. The many factors that influence the occurrence of stunting mean that one of the efforts that can be made to reduce the prevalence of stunting is to identify the factors that influence the occurrence of stunting. This study aims to determine the factors that influence the occurrence of stunting in toddlers aged 24-59 months. This research is a case control study of 75 stunted toddlers and 75 control toddlers aged 24-59 months in the Muara Delang Community Health Center working area for the period February 2023. Independent variables include family income, mother's education level, parenting style, exposure to information, exclusive breastfeeding, history of infectious diseases, dental health, the role of health cadres and the role of community leaders; while the strongest variable in this study was the incidence of stunting. The instrument used in data collection is a questionnaire, then the data will be processed using regression test data analysis. The results of the study show that the factors that influence the incidence of stunting in the Muara Delang Community Health Center work area are parenting style (p=0.049 and B=1.557), exclusive breastfeeding (p=0.005 and B=1.300), dental health (p=0.048 and B = 0.764) and family income (p=0.049 and B=0.763). Parenting style is the most influential factor in the occurrence of stunting in the Muara Delang Community Health Center working area.